Multicultural heritage in historical towns: the problems of conservation and interpretation - Rasa Čepaitienė (Lietuvos Istorijos Studijos)
In the article, the conceptions that have influenced (and still are influencing) appreciation, assimilation, and usage of the heritage accumulated in Lithuanian historical towns are analyzed, and some potential ways of solving the arising problems are proposed. It is emphasized that recognition, usage, and interpretation of cultural values accumulated in historical towns, which are, as a rule, multi-ethnic, multi-confessional, and multi-cultural, are a complex undertaking and a competence-, creativity-, and responsibility-requiring process.